Empowerment of Hijab Convection Micro Business in Kebontemu Village, Jombang Regency - Wicaksono, Agung Prasetyo Nugroho; Soelistyo, Aris (IMPOWERMENT SOCIETY, 2024)
Our community service partner is a hijab shop micro business in Nglongko Hamlet, Kebontemu Village, Peterongan District, Jombang Regency. Partners face three main problems: venture capital constraints, operational fund transparency constraints, and a monotonous marketing strategy. This community service activity aims to provide solutions to partners based on each partner's problems, namely providing venture capital assistance, computerized cash flow implementation reports, and implementing marketing through social media and marketplaces. The method used in our service is to conduct simulations and practices. The results of this community service agenda are strengthening partner business capital, implementing Excel-based cash flow reports, and implementing marketing via Instagram and the marketplace application Shopee. It is hoped that with a wider marketing reach, it will increase sales and income from Hijab shop micro business partners. In addition, with financial training, service partners can run further business ventures with better financial management.